Implementation of a Security System on a Semi-Automatic Farming Robot’s Electronic Device for ABU Robocon 2024 Using Optocoupler - Rilana, Mowi; Mowi, Mowi Rilana (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
This research aims to design and implement an optocoupler as a protective system for the electronic circuits of agricultural robots, as well as to enhance the influence of voltage and current feedback on the reliability of the system. The methodology employed involves the application of the optocoupler as an isolation between the microcontroller and the actuator load. The results of the study indicate that the application of the optocoupler in the servo driver achieves 100% efficiency in terms of safety, while in the pneumatic driver, it reaches 70%. Although the optocoupler isolation successfully prevents voltage spikes from the input side to the output side, there is a current leakage that causes the output voltage to remain at 1.499V when active LOW. The conclusion of this research emphasizes that the optocoupler is effective in protecting the electronic systems of agricultural robots from current and voltage disturbances, as well as improving system reliability through the detection of abnormal conditions.